Process of microwave assisted extraction (MAE) for Rhodomyrtus tomentosa fruit and its bioactive compounds. Issue 1 (April 2020) - Ridlo, M; Kumalaningsih, S; Pranowo, D
Abstract: Karamunting ( Rhodomyrtus tomentosa (Ait.) Hassk ) is one of the plants contains high bioactive compounds. The fruit parts have been used widely as traditional herbs in Malaysia, Vietnam, Thailand and China. In Indonesia, this plant grows as wild plants in shrubs and forests of Sumatra, Kalimantan and Sulawesi Islands. The degradation of bioactive compounds from karamunting fruit can be minimised by the extraction process. The purpose of research was to obtain the best operational condition in the extraction of the bioactive compounds from karamunting fruit. Microwave Assisted Extraction (MAE) was used in this study. MAE is a modern extraction method that utilises microwaves to increase the effectiveness and efficiency of cell breakdown. The molecular movement of microwaves produces friction and heat energy in the material so that the cell wall and tissue material will be damaged, and the solute can finally come out. The extraction process consists of 2 factor variables, namely extraction time (seconds) and solvent volume (mL). The parameters of the analysis to determine the best conditions of the extraction process were total flavonoid content (TFC), total anthocyanin content (TAC) and extract yield. The results showed that the highest yield of extract was 1.68% (v/w), the highest total flavonoid was 2563.79 mg QE/g BK, and total anthocyanin was 651.26 mg/g.